2000
DOI: 10.1083/jcb.151.5.1113
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Assembly at Kinetochores Is Uncoupled from DNA Replication

Abstract: The specification of metazoan centromeres does not depend strictly on centromeric DNA sequences, but also requires epigenetic factors. The mechanistic basis for establishing a centromeric “state” on the DNA remains unclear. In this work, we have directly examined replication timing of the prekinetochore domain of human chromosomes. Kinetochores were labeled by expression of epitope-tagged CENP-A, which stably marks prekinetochore domains in human cells. By immunoprecipitating CENP-A mononucleosomes from synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
211
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 32 publications
13
211
1
2
Order By: Relevance
“…It will therefore be critical to determine the histone/nonhistone components associated with budding yeast CenH3 by examining their localization to the CEN at precise cell cycle intervals. Such an experiment is also particularly noteworthy in light of several groups reporting the deposition of CenH3 outside of S phase (42,(46)(47)(48), a detail that has not been observed in budding yeast (19,49). Because of the ability to achieve single-nucleosome resolution, utilization of our modified ChIP protocol should clarify the protein content of the centromeric nucleosome.…”
Section: Discussionmentioning
confidence: 99%
“…It will therefore be critical to determine the histone/nonhistone components associated with budding yeast CenH3 by examining their localization to the CEN at precise cell cycle intervals. Such an experiment is also particularly noteworthy in light of several groups reporting the deposition of CenH3 outside of S phase (42,(46)(47)(48), a detail that has not been observed in budding yeast (19,49). Because of the ability to achieve single-nucleosome resolution, utilization of our modified ChIP protocol should clarify the protein content of the centromeric nucleosome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that CENP-A assembly is uncoupled from DNA replication. Although the peak of endogenous CENP-A assembly probably occurs during G2, epitope-tagged CENP-A can be assembled throughout the chromatin, and at any time during the cell cycle [7].…”
Section: Introductionmentioning
confidence: 99%
“…In human cells, centromere DNA replicates in late S phase, and CENP-A is synthesized in G 2 (31). In Drosophila melanogaster, different procedures used to study centromere replication indicated that it occurs either at early or late S phase (1,34).…”
mentioning
confidence: 99%